THE RELATIONSHIP BETWEEN THE NUTRITIONAL STATUS OF PREGNANT WOMEN AND STUNTING IN CHILDREN AGED 6-36 MONTHS AT BATUPUTIH PUBLIC HEALTH CENTER TTS REGENCY NTT PROVINCE - Rosalinda Snak; Zenia Angelina; Dewa Ayu Liona Dewi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Introduction: Based on data from February 2021 at the Batuputih Health Center, TTS Regency, NTT Province, there were 23.6% of toddlers experiencing stunting, meaning that the incidence of stunting at the Batuputih Health Center is still high. Objective: To determine the relationship between the nutritional status of pregnant women and the incidence of stunting in children aged 6-36 months at Batuputih Health Center. Methods: The research design used was cross-sectional. The study population was all children under five who were registered at Batuputih Health Center in February 2021 as many as 1423 people. The sample of children aged 6-36 months who met the criteria were 708 people and were selected using simple random sampling as many as 72 people were calculated using the Lameshow formula. The dependent variable is stunting and the independent variable is the nutritional status of pregnant women based on LiLA. The data was taken from medical records and then analyzed using the Coefficient Contingency correlation test. Results: There were 29 (40.3%) pregnant women with SEZ and 43 (59.7%) pregnant women with normal nutritional status. There were 19 (26.4%) stunting toddlers and 53 (73.6%) normal toddlers. Pregnant women with SEZ who have stunting toddlers are 13 (18.1%) and 16 (22.2%) normal toddlers. Pregnant women with normal nutritional status who have stunting under five as many as 6 (8.3%) people and toddlers with normal nutritional status 37 (51.4%) people. Statistical test results obtained p of 0.004 (p <0.05), r of 0.325. Conclusion: There is a significant relationship between poor nutritional status of pregnant women and the incidence of stunting in toddlers aged 6-36 months (p = 0.004), the r value is 0.325.Keywords: Nutritional status of pregnant women, stunting